Innovation as the basis of the country's public policy development - Oleksenko, Roman; Олексенко, Роман Іванович; Олексенко, Роман Иванович (My University, 2020)
The chosen theme of innovation as the basis for the public policy development is extremely important for our country development under the current economic conditions, because the effective functioning of a market economy is possible only if there are certain external and internal factors in the country that provide a favorable basis for the entrepreneurship development.
Keywords: economy; development; market economy